2011
DOI: 10.1111/j.1755-0998.2011.03047.x
|View full text |Cite
|
Sign up to set email alerts
|

Prey DNA detection success following digestion by intraguild predators: influence of prey and predator species

Abstract: Intraguild predation (IGP) has been increasingly recognized as an important interaction in ecological systems over the past two decades, and remarkable insights have been gained into its nature and prevalence. We have developed a technique using molecular gut-content analysis to compare the rate of IGP between closely related species of coccinellid beetles (lady beetles or ladybirds), which had been previously known to prey upon one another. We first developed PCR primers for each of four lady beetle species: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 80 publications
6
60
0
2
Order By: Relevance
“…Because of the difficulty of analyzing gut content, especially for small arthropods, very few quantitative data are available for gut capacity and digestion time of insects. However, PCRbased gut content analysis in ladybeetles revealed that prey DNA detection time, an indirect measure of digestion time, varied from 1 to 19 h depending on the predator species and prey species and size (Hoogendoorn and Heimpel 2001, McMillan et al 2007, Gagnon et al 2011. Our estimates of the corrected digestion FIG.…”
Section: Discussionmentioning
confidence: 85%
“…Because of the difficulty of analyzing gut content, especially for small arthropods, very few quantitative data are available for gut capacity and digestion time of insects. However, PCRbased gut content analysis in ladybeetles revealed that prey DNA detection time, an indirect measure of digestion time, varied from 1 to 19 h depending on the predator species and prey species and size (Hoogendoorn and Heimpel 2001, McMillan et al 2007, Gagnon et al 2011. Our estimates of the corrected digestion FIG.…”
Section: Discussionmentioning
confidence: 85%
“…H. axyridis also practices indirect intraguild predation on aphid parasitoids, because it preferentially consumes parasitized aphids over uninfected ones . Laboratory and field studies of intraguild predation involve both visual observations and, more recently, the screening of gut contents by DNA analysis (e.g., Gagnon et al, 2011;Rondoni et al, 2015). Such studies have repeatedly indicated that intraguild predation behavior is important for the invasion success of H. axyridis.…”
Section: Intraguild Predationmentioning
confidence: 99%
“…This was confirmed by Gagnon et al (2011a), who used this method to investigate IGP interactions between different ladybirds, including H. axyridis. Despite close taxonomic relations between the different predators and prey, the half-life of the period for which the DNA of the prey could be detected recorded in the latter study ranged from 5.2 to 19.3 h. In our study, the level of detection of the DNA of prey also differed for the different species of prey, supporting the conclusion of McMillan et al (2007) and Gagnon et al (2011a) that detection times cannot be generalized even if predators and prey are closely related and DNA fragments from the same region and of similar length are targeted.…”
Section: Discussionmentioning
confidence: 63%
“…Agusti et al, 2003;Hosseini et al, 2008). The half-life of the period for which prey DNA could be detected for each predator-prey combination ranged from 8.9 to 52.4 h; the long half-life for fourth instar H. axyridis feeding on C. carnea indicates it is possible to detect relatively rare predation events (Gagnon et al, 2011a). However, long detection periods could obscure the frequency of predatory events in the field, since recent feeding events are not distinguishable from older ones, and could lead to overestimation of predation rates.…”
Section: Discussionmentioning
confidence: 99%